Outcomes of Injection Laryngoplasty for Deep Interarytenoid Groove - Kelsey H. Mothersole; Seckin O. Ulualp; Romaine F. Johnson; Ashley F. Brown; Gopi B. Shah; Christopher C. Liu; Stephen R. Chorney (International Archives of Otorhinolaryngology, 2024)
Introduction Deep interarytenoid groove (DIG) may cause swallowing dysfunction in children; however, the management of DIG has not been established.